A phase II randomized clinical trial to assess toxicity and quality of life of breast cancer patients with hypofractionated versus conventional fractionation radiotherapy with regional nodal irradiation in the context of COVID-19 crisis - Gil, Gabriel Oliveira Bernardes; de Andrade, Warne Pedro; Diniz, Paulo Henrique Costa; Cantidio, Farley Soares; Queiroz, Izabella Nobre; Gil, Maria Luísa Braga Vieira; Almeida, Conceição Aparecida Medeiros; Caldeira, Paola Palmer Reis; Regalin, Marcos; Silva-Filho, Agnaldo Lopes (Frontiers in Oncology, 2023)
PURPOSE: This study, conduct in COVID-19 crisis, primarily aimed to compare the acute toxicity between conventional fractionated radiation therapy (CF-RT) with hypofractionated radiation therapy (HF-RT) among patients underwent breast-conserving surgery or mastectomy in whose breast or chest wall and regional nodal irradiation (RNI) was indicated. The secondary endpoints were both acute and subacute toxicity, cosmesis, quality of life, and lymphedema features. METHODS: In this open and non-inferiority randomized trial, patients (n= 86) were randomly 2:1 allocated in CF-RT arm (n = 33; 50 Gy/25 fractions ± sequential boost [10 Gy/5 fractions]) versus HF-RT arm (n = 53; 40 Gy/15 fractions ± concomitant boost [8 Gy/15 fractions]). Toxic effects and cosmesis evaluation used the Common Terminology Criteria for Adverse Events version 4.03 (CTCAE) and the Harvard/NSABP/RTOG scale. For patients-reported quality of life (QoL), European Organization for Research and Treatment of Cancer quality of life questionnaire (EORTC QLQ-C30) and the breast cancer-specific supplementary questionnaire (QLQ-BR23) were used. Lymphedema was assessed by comparing volume differences between the affected and contralateral arms, as Casley-Smith formula. RESULTS: Grade 2 and grade 3 dermatitis were lower with HF-RT than with CF-RT (28% vs. 52%, 0% vs. 6%; p = 0.022, respectively). HF-RT had lower rate of grade 2 hyperpigmentation (23% vs. 55%; p = 0.005), comparing to CF-RT. No other differences in overall rates of physician-assessed grade 2 or higher and grade 3 or higher acute toxicity between HF-RT vs. CF-RT were registered. There was no statistical difference between groups regarding cosmesis, lymphedema rate (13% vs. 12% HF-RT vs. CF-RT; p = 1.000, respectively), as well as functional and symptom scales, both during the irradiation period and after six months of the treatment ending. The results revealed that the subset of patients up to 65 years or older did not show a statistical difference between both arms fractionation schedules (p > 0.05) regarding skin rash, fibrosis, and lymphedema. CONCLUSION: HF-RT was non-inferior to CF-RT and moderate hypofractionation showed lower rates of acute toxicity, with no changes in quality-of-life outcomes.